Good intentions, bad behavior: A review and synthesis of the literature on unethical prosocial behavior (UPB) at work - Mo, Shenjiang; Lupoli, Matthew J.; Newman, Alexander; Umphress, Elizabeth E. (Journal of organizational behavior, 2023)
Summary Scholars have investigated work behaviors that are intended to help others, yet at the same time violate societal values, norms, laws, or standards of proper conduct. We refer to these actions collectively as unethical prosocial behavior (UPB) at work. In this paper, we provide a critical review of the UPB literature. Our review makes several contributions: First, we clarify definitional issues surrounding UPB, while also offering suggestions for the improvement of measurement and methodology in the study of UPB. Second, we review the major theoretical perspectives that have been adopted in empirical research on UPB at different levels of analysis and summarize the empirical findings on the topic. In doing so, we highlight the theoretical and empirical challenges facing this work. Finally, we develop an agenda for future research that clears a path toward resolving these issues and advancing knowledge of UPB.